Advanced instrumentation and computer I/O design real-time system computer interface engineering - Garrett, Patrick H. (IEEE Press, 1994)
This advanced text addresses system error analysis and performance accountability in a comprehensive and up-to-date manner. Covering a wide range of topics from instrumentation, sensors, and signal conditioning through digital conversion and signal reconstruction, the author employs model-based methods for characterizing the design and analysis of real-time computer I/O systems.